Only SF3B1 mutation involving K700E independently predicts overall survival in myelodysplastic syndromes. Issue 19 (23rd June 2021) - Kanagal‐Shamanna, Rashmi; Montalban‐Bravo, Guillermo; Sasaki, Koji; Darbaniyan, Faezeh; Jabbour, Elias; Bueso‐Ramos, Carlos; Wei, Yue; Chien, Kelly; Kadia, Tapan; Ravandi, Farhad; Borthakur, Gautam; Soltysiak, Kelly A.; et al.
Abstract : Background: SF3B1 mutations ( SF3B1 mut ) in myelodysplastic syndromes (MDS) frequently involve codon K700E and have a favorable prognosis. The prognostic effect of non‐K700E SF3B1 mut is uncertain. Methods: The authors analyzed the clinicopathological features and outcomes of a single‐institution series of 94 treatment‐naive SF3B1 mut MDS patients (18%) and 415 treatment‐naive SF3B1 wt MDS patients and explored the differences between K700E and non‐K700E SF3B1 mut MDS. Results: Fifty‐five patients (59%) carried K700E. Recurrent non‐K700E mutations (39 [41%]) included R625, H662, and K666. Compared with SF3B1 mut K700E patients, non‐K700E patients had a lower median absolute neutrophil count (1.8 vs 2.4; P = .005) and were frequently "high" according to the Revised International Prognostic Scoring System (19% vs 4%; P = .031). Non‐K700E MDS was associated frequently with RUNX1 (26% vs 7%; P = .012) and exclusively with BCOR, IDH2, and SRSF2 mutations. A splicing analysis showed the differential distribution of alternatively spliced events and gene expression profiles between K700 and non‐K700E MDS patients. The majority (at least 80%) of SF3B1 mut K700E, SF3B1 mut non‐K700E, and SF3B1 wt patients were treated with hypomethylating agents. Over a median follow‐up of 16 months, SF3B1 mut had superior overall survival (OS) in comparison with SF3B1 wt in all MDS patients (not reached vs 25.2 months; P = .0003), in patients with low‐grade MDS, and in patients with myelodysplastic syndromes with ring sideroblasts (MDS‐RS). Compared with SF3B1 wt, SF3B1 mut K700E had superior outcomes in all MDS (median OS, 25 months vs not reached; P = .0001), in low‐grade MDS (median OS, 41.3 months vs not reached; P = .0015), and in MDS‐RS (median OS, 22.3 months vs not reached; P = .0001), but no significant difference was seen between non‐K700E and SF3B1 wt MDS. By multivariable analysis, the absence of SF3B1 mut K700E mutations was independently associated with the prognosis. Conclusions: This study highlights the importance of the SF3B1 mutation subtype in MDS risk assessment. Lay Summary: Myelodysplastic syndromes (MDS) with SF3B1 mutations are regarded as having a favorable prognosis by both the World Health Organization and the International Working Group for the Prognosis of Myelodysplastic Syndromes. However, this article shows that only MDS patients with SF3B1 K700E mutations have a favorable prognosis (and not MDS patients with SF3B1 mutations involving other codons). This has important implications for refining future MDS subclassification and risk assessment criteria. Abstract : Myelodysplastic syndromes (MDS) with K700E and non‐K700E SF3B1 mutations show distinct clinicopathological and genomic characteristics, with only SF3B1 K700E mutated MDS showing significantly better overall survival compared to wild‐type MDS. The SF3B1 mutation type is important for MDS risk assessment.